2019
DOI: 10.1001/jamanetworkopen.2019.12458
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Rotavirus Vaccination and Risk of Intussusception Among Neonates and Infants

Abstract: This systematic review and meta-analysis assesses the association of rotavirus vaccination among neonates and infants with risk of intussusception for up to 2 years after vaccination overall and by type of vaccine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
17
0
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 44 publications
2
17
0
2
Order By: Relevance
“…Examination of intestinal biopsies from rotavirus-infected children, however, show poor correlation between histological abnormalities and diarrhoea (K€ ohler et al 1990;Ramig 2004;. Interestingly, rotavirus-induced anatomical changes were linked to the slightly increased intussusception (a serious condition where an intestinal segment folds into an adjacent part of the intestine) observed primarily in application of the firstgeneration vaccine, but more substantial evidence has demonstrated that neither natural rotavirus infection nor vaccination are significantly associated with intussusception (Robinson et al 2004;Lu et al 2019;. In general, rotavirus-induced gastrointestinal disease manifests as acute gastroenteritis is associated with watery diarrhoea, low-grade fever, vomiting, low inflammation, and intestinal wall damage (Hagbom et al 2020).…”
Section: Acute Gastroenteritismentioning
confidence: 99%
“…Examination of intestinal biopsies from rotavirus-infected children, however, show poor correlation between histological abnormalities and diarrhoea (K€ ohler et al 1990;Ramig 2004;. Interestingly, rotavirus-induced anatomical changes were linked to the slightly increased intussusception (a serious condition where an intestinal segment folds into an adjacent part of the intestine) observed primarily in application of the firstgeneration vaccine, but more substantial evidence has demonstrated that neither natural rotavirus infection nor vaccination are significantly associated with intussusception (Robinson et al 2004;Lu et al 2019;. In general, rotavirus-induced gastrointestinal disease manifests as acute gastroenteritis is associated with watery diarrhoea, low-grade fever, vomiting, low inflammation, and intestinal wall damage (Hagbom et al 2020).…”
Section: Acute Gastroenteritismentioning
confidence: 99%
“…The second tragedy occurred in 1955 when a non-fully inactivated poliovirus vaccine was given to more than 100,000 children, causing several cases of paralysis. Aside from these 2 tragedies, it has been noted that 1 in 2.5 million oral polio vaccinees may develop paralysis, and the original rotavirus vaccine was associated with intussusception in 1 in 100,00 vaccinees [ 9 ]. As a result, all of the serious adverse reactions are now well documented as potential side effects for a number of different vaccines.…”
Section: Adverse Reactions To Vaccinationmentioning
confidence: 99%
“… 20 Rare events, such as intussusception after the use of oral rotavirus vaccines, might not be apparent, even in trials of 30 000–60 000 people. 21 Vaccine-associated enhanced respiratory disease and antibody-dependent enhancement were reported in animals given vaccines against SARS-CoV and MERS-CoV; 22 fortunately, these effects have not been reported in small animal, non-human primate, or human studies of SARS-CoV-2 vaccines. 23 However, a long-term effect, similar to the enhancement that was observed for the Sanofi dengue virus vaccine, cannot be ruled out.…”
Section: Lmic Challenges and Opportunitiesmentioning
confidence: 99%